Motets à I, II, III, IV et V parties, avec symphonies et basse continue - Lorenzani, Paolo 1640-1713 (Paris Ballard, 1693)
In 1678, Lorenzani traveled to Paris, hoping to find fortune. His motets were performed for Louis XIV, who recognized his talent and appointed him music master to the queen. Under orders of the king, Lorenzani traveled back to Italy and recruited singers for the monarch's chapel. Despite assistance from Madame de Montespan, he never achieved sufficient popularity to overcome great antagonism from Jean-Baptiste Lully.
Guillo 2021 n° 1693-A; RISM L 2834
7 out of 11 parts: HC, HT, B, t/b du grand choeur, vn1, vn2, bdv
No title-page, but dedication
Keywords: Château de Versailles (France); 17th Century (1601-1700); Motet; Court; Catholicism; Versailles (France)